Modelling of a pneumatic actuator - Felix, Roger Oliva [UNESP]; Bueno, Átila Madureira [UNESP] (Praise Worthy Prize, 2019)
This paper refers to the modelling of a pneumatic actuator coupled to a mechanical system (mass-spring-damper). These actuators contain a clean technology compared to hydraulic actuators, a good relation between power and mass supported, and low cost in relation to electric actuators. In order to develop the modelling, it is needed to determine the motion equation by the Lagrange method, calculating the system energies (kinetic energy, potential energy, and dissipative energy of Rayleigh). This modelling is performed for a fluidic system with constant pressure differential and a fluidic system with variable pressure differential, applying a pressure with harmonic characteristics. Moreover, with the application of the numerical simulations to this model, it is possible to find similar responses to the real system. Thus, it is demonstrated that the facility of modelling of the pneumatic actuator occurs due to the coupling of the mechanical system. The numerical responses are obtained as a function of time and in the phase plane in order to analyze the equilibrium type of the system.
Keywords: Equilibrium types; Lagrange method; Mechanical system; Numeric simulation